2007
DOI: 10.7773/cm.v33i4.1148
|View full text |Cite
|
Sign up to set email alerts
|

Structure of rhodolith beds from 4 to 55 meters deep along the southern coast of Espírito Santo State, Brazil

Abstract: Rhodoliths are one of the most extensive benthic communities of the Brazilian continental shelf, but their structure is poorly known. The richest marine flora of Brazil´ s coastal zone is found in Espírito Santo State and its diversity has been partly associated with the presence of extensive areas of rhodoliths, extending from the intertidal zone to 120 m across the continental shelf. One species of kelp, Laminaria abyssalis, is endemic to this area and occurs between 45 and 120 m depth. Our objective was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(83 citation statements)
references
References 16 publications
5
64
1
6
Order By: Relevance
“…2006, Amado-Filho et al 2007). En un estudio reciente, Amado-Filho et al (2007) observaron un aumento en la talla de rodolitos individuales ( fig.…”
Section: Methodsunclassified
See 4 more Smart Citations
“…2006, Amado-Filho et al 2007). En un estudio reciente, Amado-Filho et al (2007) observaron un aumento en la talla de rodolitos individuales ( fig.…”
Section: Methodsunclassified
“…In a recent study, Amado-Filho et al (2007) showed that individual rhodoliths ( fig. 1b) occurring from 4 to 55 m depth along the southern coast of Espírito Santo increased in size and their density decreased from the shallow to the deeper zones; however, studies are required to determine how this rhodolith distribution Los rodolitos, las formas de vida libre de varios géneros de algas coralinas no geniculadas, también han sido reconocidos como especies fundamentales (Amado-Filho et al 2007, Foster et al 2007). La diversidad de los organismos que viven sobre los rodolitos probablemente sea resultado de que proporcionan superficies duras para la fijación (Foster et al 2007).…”
Section: Diversidad De Macroalgas Asociada Con Un Manto De Rodolitos unclassified
See 3 more Smart Citations